2023
DOI: 10.3390/v15020459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serological Methods for Tick-Borne Encephalitis Virus-Specific Antibody Detection in Wild Boar and Sheep: Impact of the Screening Approach on the Estimated Seroprevalence

Abstract: Tick-borne encephalitis virus (TBEV) is a flavivirus transmitted by ticks. Serological screenings in animals are performed to estimate the prevalence and distribution of TBEV. Most screenings consist of a primary screening by ELISA, followed by confirmation of positive samples by plaque reduction neutralization tests (PRNTs). In this study, 406 wild boar sera were tested with 2 regularly used commercial ELISAs for flavivirus screening in animals (Immunozym FSME (TBEV) IgG All Species (Progen) and ID Screen Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 60 publications
8
11
2
Order By: Relevance
“…When we used optimal cutoff weighting sensitivity and speci city equally for cattle sera, ID Screen® cELISA still showed a signi cantly lower ability to detect positive cattle (Se, 64.5%) than Immunozym cELISA (Se, 78.1%). This low ability to detect TBEV antibodies in different mammal species has already been observed in previous studies (35,(37)(38)(39). In these studies, the sensitivity of Immunozym cELISA was even lower than ours, with a sensitivity of 57% in goats (35), 42% in foxes (38) and 23% in wild boar sera (37), even all considering borderline results as positive.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…When we used optimal cutoff weighting sensitivity and speci city equally for cattle sera, ID Screen® cELISA still showed a signi cantly lower ability to detect positive cattle (Se, 64.5%) than Immunozym cELISA (Se, 78.1%). This low ability to detect TBEV antibodies in different mammal species has already been observed in previous studies (35,(37)(38)(39). In these studies, the sensitivity of Immunozym cELISA was even lower than ours, with a sensitivity of 57% in goats (35), 42% in foxes (38) and 23% in wild boar sera (37), even all considering borderline results as positive.…”
Section: Discussionsupporting
confidence: 56%
“…Both of them are frequently used for screening in large TBEV serological surveys conducted on wild and domestic fauna. These commercial kits have been compared for the detection of TBEV antibodies in various species, but not in cattle and not always by adapting the threshold values to the targeted species (35,(37)(38)(39). Recently, one study, although based on a very limited number of TBEV positive samples, have shown that their capacity to detect positive samples was especially low when seroneutralising antibody titres were low (37).…”
Section: Introductionmentioning
confidence: 99%
“…When we used optimal cutoff weighting sensitivity and specificity equally for cattle sera, ID Screen® cELISA still showed a significantly lower ability to detect positive cattle (Se, 64.5%) than Immunozym cELISA (Se, 78.1%). This low ability to detect TBEV antibodies in different mammal species has already been observed in previous studies [35,[37][38][39]. In these studies, the sensitivity of Immunozym cELISA was even lower than ours, with a sensitivity of 57% in goats [35], 42% in foxes [38] and 23% in wild boar sera [37], even all considering borderline results as positive.…”
Section: Discussionsupporting
confidence: 53%
“…Both of them are frequently used for screening in large TBEV serological surveys conducted on wild and domestic fauna. These commercial kits have been compared for the detection of TBEV antibodies in various species, but not in cattle and not always by adapting the threshold values to the targeted species [35,[37][38][39]. Recently, one study, although based on a very limited number of TBEV positive samples, has shown that their capacity to detect positive samples was especially low when seroneutralising antibody titres were low [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation